Establishment of papillary thyroid cancer organoid lines from clinical specimens - Yang, Hao; Liang, Qingzhuang; Zhang, Jian; Liu, Jinkun; Wei, Hao; Chen, Haibo; Wei, Wei; Chen, Dong; Zhao, Yongsheng (Frontiers in Endocrinology, 2023)
Papillary thyroid cancer (PTC) is a common malignancy of the endocrine system, and its morbidity and mortality are increasing year by year. Traditional two-dimensional culture of cell lines lacks tissue structure and is difficult to reflect the heterogeneity of tumors. The construction of mouse models is inefficient and time-consuming, which is difficult to be applied to individualized treatment on a large scale. Clinically relevant models that recapitulate the biology of their corresponding parental tumors are urgently needed. Based on clinical specimens of PTC, we have successfully established patient-derived organoids by exploring and optimizing the organoid culture system. These organoids have been cultured stably for more than 5 passages and successfully cryopreserved and retried. Histopathological and genome analysis revealed a high consistency of the histological architectures as well as mutational landscapes between the matched tumors and organoids. Here, we present a fully detailed method to derive PTC organoids from clinical specimens. Using this approach, we have developed PTC organoid lines from thyroid cancer samples with a success rate of 77.6% (38/49) until now.